The impact of a graphic novel on anxiety and stress in patients undergoing endoscopic ultrasound with fine needle biopsy for pancreatic lesions: a pilot study protocol - Rizzo, Giacomo Emanuele Maria; Traina, Mario; Tarantino, Ilaria (Frontiers in Gastroenterology, 2024)
The utilization of graphic novels in the realm of clinical medicine is an infrequent occurrence. However, there is a burgeoning interest in their application across a spectrum of pathological conditions with the ultimate aim of enhancing patient care. This study is a prospective pilot designed to assess the influence of graphic novels on the stress levels and behavioral responses of patients diagnosed with pancreatic lesions and who are to undergo endoscopic ultrasound-guided fine needle biopsy (EUS-FNB). Patients exhibiting radiological and clinical pancreatic lesions needing biopsy will be evaluated consecutively. The inclusion criteria encompass the presence of a solid pancreatic mass or a partially solid mass in the event of a cystic component. The exclusion criteria include patients with cognitive impairments, those currently on benzodiazepines or other psychotropic medications, and those with a prior diagnosis of cancer. The authors have developed a comic panel comprising a sequence of six vibrant vignettes, which delineate the standard procedure of EUS-FNB to the patient. Following hospital admission, patients who meet the enrolment criteria and consent to participate in the study will be randomly assigned to either the test or the control group. A graphic novel will be distributed to all patients in the test group, who will have the opportunity to peruse it while awaiting the procedure. Subsequent to the EUS-FNB, all enrolled patients will complete the Beck Anxiety Inventory (BAI) and a modified version of the Depression Anxiety Stress Scales-21 (termed mDASS-21 or mASS-14). The BAI, a 21-item self-report inventory, is employed to gauge the severity of anxiety in adults. The other questionnaire is a modified rendition of the DASS-21, which originally comprised 21 items segregated into three subscales (anxiety, stress, and depression) with seven items each. The anxiety subscale measures physiological arousal, situational anxiety, and the subjective experience of the effects of anxiety, while the stress subscale assesses chronic non-specific arousal, difficulty relaxing, nervous tension, irritability, agitation, and impatience.